Pengaruh Dana Alokasi Khusus terhadap Indeks Pembangunan Manusia dengan Mediasi Belanja Modal di Sulawesi Selatan - Andi Marwah Nur; Diah Retno Dwi Hastuti; Muhammad Syafri; Sri Astuty; Shadry Andriani (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The Human Development Index (HDI) is a key indicator for assessing the success of regional development through improvements in the quality of life of the population. Although the HDI in South Sulawesi has shown an increasing trend and is classified in the high category, the effectiveness of regional fiscal instruments, particularly the Special Allocation Fund (DAK) and capital expenditure, remains a critical concern in enhancing the sustainability of human development outcomes. Based on public finance theory and human capital theory, government budget allocation to productive sectors has the potential to improve the quality of human resources through the provision of basic public services. This study aims to analyze the effect of the Special Allocation Fund on capital expenditure, examine the impact of both the Special Allocation Fund and capital expenditure on the Human Development Index, and test the mediating role of capital expenditure across districts and municipalities in South Sulawesi for the period 2011–2024. This research employs a quantitative approach using panel data through two estimation models, namely the random effects model and the fixed effects model, as well as the Sobel test to examine the mediation effect. The results indicate that the Special Allocation Fund has a significant effect on capital expenditure, capital expenditure significantly influences the Human Development Index, and the Special Allocation Fund also affects the Human Development Index both directly and indirectly through capital expenditure. These findings suggest that optimizing the allocation of the Special Allocation Fund through productive capital expenditure contributes to the improvement of human development.